Circle nephrostomy tube revisited - Noureldin, Yasser A.; Diab, Christian; Valenti, David; Andonian, Sero (Canadian Urological Association Journal, 2016)
Introduction: There are few options for patients requiring chronic urinary drainage using nephrostomy tubes. Although circle nephrostomy tube (CNT) was invented in 1954, it is rarely used. Its advantages include longer indwelling time such that it is changed semi-annually when compared with the standard nephrostomy tube (SNT), which is changed monthly. However, there are no studies comparing indwelling times and costs with these two tubes. The aim of the present study was to compare CNT with SNT in terms of frequency of tube changes, reasons for earlier tube changes, and associated costs. Methods: Patients who had CNT inserted between 2009 and 2015 were reviewed. The indications for chronic indwelling nephrostomy tubes were tabulated. The frequency of tube changes was compared between CNT and SNT in the same patients. Furthermore, costs associated with insertion and exchange of CNT and SNT were analyzed. Results: Seven patients with mean age of 71.9 ± 7.6 years (range 43‒96) had a total of 36 CNT changes. The mean number of CNT changes was four (range 2‒5) at a mean interval of 168.3 ± 15.6 days (range 120‒231). All patients had SNT prior to converting to CNT. When compared with the mean interval for SNT changes, the mean interval for CNT changes was significantly longer (44.8 ± 19.4 vs. 168.3 ± 41.3 days; p=0.028). Tube blockage and urinary leakage were the most common reasons for earlier than scheduled CNT changes. In our centre, CNT insertion and exchange cost $1965.48 and $923.96 compared with $1450.43 and $803.81 for SNT, respectively. There was an estimated cost savings of $46 861.10 (range $87 414.30 –$40 553.20) for the whole cohort by switching from SNTs to CNTs. Conclusions: Despite the small sample size as the main limitation, this study confirms that CNTs are associated with significantly fewer changes and lower cost when compared with SNTs for poorsurgical- risk patients requiring chronic NTs.